Promovendo saúde através da acupuntura associada ao alongamento passivo na redução da dor lombar e no ganho de flexibilidade em estudantes universitários - Martins, Raphael Cezar Carvalho (2008)
The association of acupuncture and kinesiotherapy techniques is an innovative proposal when the objective of therapeutic approach is to perform a diagnosis and treatment of muscle-skeletal pathologies, such as pain in lumbar column, merging a holistic vision of acupuncture and a limited vision of traditional occidental techniques. The aim of the present study is to compare passive muscular streching associated with acupuncture and passive muscular streching alone, considering the gain in movement amplitude, flexibility and the improving the algesic state on lumbar portion of spinal column in undergraduate students with age between 20 and 30 years from FPM - Faculdade Patos de Minas. The study was performed with a random sample of 15 students divided in three groups of five individual in each group. In group A there were performed five sessions of treatment with acupuncture; in group B there were performed five sessions of treatment with kinesioacupuncture; and finally, in group C there were performed five sessions of treatment with kinesiotherapy. Collected data was submitted to Wilcoxon test for statistical analysis of the results. We can conclude, in this study, that association of acupuncture with passive muscular streching (kinesioacupuncture) was statistically relevant in the improvement of flexibility and reduction of “algesic state” on lumbar portion of spinal column, when compared to passive muscular streching or acupuncture alone; despite of passive muscular streching have been demonstrated to be the best technique for this porpuse. Key-words: kinesioacupuncture; lumbar pain; muscular stretching; acupuncture.